Endocrine regimen and early subclinical atherosclerosis in premenopausal HR+/HER2− breast cancer: real-world evidence and regimen-dependent effects of Sanhuang Decoction - Hong, Ke; Wang, Cong; Yang, Menglei; Du, Mengyue; Wang, Huanhuan; Wu, Jiawei; Liu, Xinhe; Li, Xiaoyu; Wu, Wenjie; Li, Shuqin; Cheng, Hongyu; Yao, Chang (Frontiers in Oncology, 2026)
IntroductionAdjuvant endocrine therapy for hormone receptor–positive, human epidermal growth factor receptor 2–negative (HR+/HER2−) breast cancer improves survival but may worsen cardiometabolic health; the cardiovascular impact of aromatase inhibitor plus ovarian function suppression (AI+OFS) in premenopausal women remains unclear. We compared endocrine regimens on subclinical atherosclerosis and 24-month lipid trajectories and explored potential modulatory effects of Sanhuang Decoction (SHD).MethodsIn this retrospective cohort of 280 HR+/HER2− patients, initial endocrine therapy was AI+OFS (n = 95), tamoxifen (TAM; n = 141), or TAM+OFS (n = 44). Lipid profiles (total cholesterol, triglycerides, low-density lipoprotein cholesterol [LDL-C], high-density lipoprotein cholesterol [HDL-C]) were analyzed using mixed-effects models adjusted for cardiometabolic and treatment covariates. New-onset or worsening fatty liver, new-onset carotid plaque, and initiation of lipid-lowering therapy were evaluated with Kaplan–Meier and Cox models.ResultsIn adjusted mixed-effects models, AI+OFS versus TAM was associated with higher LDL-C (β 0.088 mmol/L; 95% confidence interval [CI] 0.013–0.163) and lower HDL-C (β −0.046 mmol/L; 95% CI −0.090 to −0.003), whereas total cholesterol and triglycerides did not differ between regimens. Incidences of fatty liver, carotid plaque, and initiation of lipid-lowering therapy varied across groups, but most adjusted Cox models showed no significant regimen effects. AI+OFS showed a trend toward a higher hazard of new-onset carotid plaque versus TAM (hazard ratio [HR] 3.09; 95% CI 0.96–9.93), and higher baseline glycated hemoglobin predicted earlier initiation of lipid-lowering therapy (HR 2.54; 95% CI 1.29–4.99). In exploratory interaction analyses, among SHD users TAM+OFS versus TAM was associated with lower LDL-C and total cholesterol, whereas in AI+OFS versus TAM SHD use was associated with lower HDL-C.ConclusionIn premenopausal women with HR+/HER2− breast cancer, AI+OFS was associated with an adverse lipid profile and a possible increase in carotid plaque compared with TAM-based regimens. Regimen-dependent associations between SHD and lipid profiles support individualized cardiovascular monitoring and cautious use of adjunctive SHD in this population.